Penerapan Model Pembelajaran Group Investigation dalam Meningkatkan Hasil Belajar Biologi pada Siswa Kelas XI MIA di SMA Negeri 3 Pematangsiantar - Huda, Muhammad Komarul (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study assesses the impact of implementing the Group Investigation (GI) Learning Model on the Biology learning outcomes of grade XI MIA students at SMA Negeri 3 Pematangsiantar. Employing a quasi-experimental design, two experimental groups applied the GI Learning Model, while the control group received conventional teaching. Results revealed a significant enhancement in Biology learning outcomes for the experimental groups, as reflected in improved pre-test and post-test scores. Conversely, the control group exhibited no noteworthy changes. Student responses conveyed a high level of satisfaction with the GI Learning Model in the context of Biology education. These findings recommend educators and policymakers consider GI Learning Model implementation as an effective alternative for enhancing Biology learning outcomes in high schools. Further research is necessary to explore factors influencing the success of this model, along with its implications for curriculum development and teaching methods.